Atomistic simulation of the mechanical response of a nanoporous body-centered cubic metal - Ruestes, Carlos Javier (2013)
Uniaxial strain compression of a Ta monocrystal containing randomly placed nanovoids was studied using molecular dynamics simulations. Interacting voids decrease the stress required for the onset of plasticity, in comparison with earlier studies for isolated voids. Dislocations resulting from loading are emitted from void surfaces as shear loops, with their interactions leading to hardening. Plastic activity leads to a decrease in porosity, with voids disappearing at 14% strain. The resulting dislocation densities agree well with experimental results.